MODEL MATEMATIKA MANGSA PEMANGSA TIGA SPESIES DENGAN FUNGSI RESPON HOLLING TIPE II DAN HOLLING TIPE IV SERTA PEMANENAN PADA POPULASI MANGSA - TYAN HIDAYATUS SHOLIHAH (Universitas Negeri Surabaya, 2020)
In this world, living things are interdependent. Every living creature needs another living creature, so there is an interaction between the two. One of interactions that occur in mini style is predator prey interaction. The interaction of prey and predator in the world of ecology is an important and interesting thing to discuss. Therefore many researchers make mathematical models of predator prey to find out the interacions of these prey predators. In this study involved three species, namely two species of prey and one species of predator. Concerning predatory prey behavior with Holling type II, and Holling type IV response functions and harvesting in second prey populations. In this study, the type IV Holling function is used when the predator preys on the first prey, and the type II Holling response function is used when the predator preys on the second prey. This research is a type of quantitative research that examines theories and concepts relating to the problems discussed in this study through various literature sources. This article specifically discusses concerning the construction of predator prey models with Holling type II, and Holling type IV response functions as well as harvesting in the second prey population models obtained from the results of construction in this study are in equation (21).